2023
DOI: 10.3390/ijms24108809
|View full text |Cite
|
Sign up to set email alerts
|

Potential Function of Testicular MicroRNAs in Heat-Stress-Induced Spermatogenesis Disorders

Abstract: Spermatogenesis is temperature-dependent, and the increase in testicular temperature seriously affects mammalian spermatogenesis and semen quality. In this study, the testicular heat stress model of mice was made with a 43 °C water bath for 25 min, and the effects of heat stress on semen quality and spermatogenesis-related regulators were analyzed. On the 7th day after heat stress, testis weight shrank to 68.45% and sperm density dropped to 33.20%. High-throughput sequencing analysis showed that 98 microRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Similarly, miR-143-3p and miR-92a-3p, which were downregulated in high temperature treated fish in the present study, were altered in mice testes exposed for only 25 minutes to elevated temperatures, highlighting them as potential markers in heat-induced spermatogenesis disorder (Gan et al, 2023). Higher levels of circulating miR-143 and miR-223 were detected in plasma levels together with cortisol after acute stress response in E. sea bass (Houdelet et al, 2023), similarly of what observed in this study by heat stress.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similarly, miR-143-3p and miR-92a-3p, which were downregulated in high temperature treated fish in the present study, were altered in mice testes exposed for only 25 minutes to elevated temperatures, highlighting them as potential markers in heat-induced spermatogenesis disorder (Gan et al, 2023). Higher levels of circulating miR-143 and miR-223 were detected in plasma levels together with cortisol after acute stress response in E. sea bass (Houdelet et al, 2023), similarly of what observed in this study by heat stress.…”
Section: Discussionsupporting
confidence: 65%
“…In literature, miR-129 was associated with sexual maturity in rainbow trout (Oncorhynchus mykiss) testis (Farlora et al, 2015) while miR-724-5p (referred to as miR-724-x), showed upregulation during oocyte maturation although it suppressed cyp19a1a (Guiguen et al, 2010;Zhang et al, 2022). In mice (Gan et al, 2023), miR-143-3p was shown to be highly upregulated after heat-induced stress reducing spermatogenesis and thus indicating the thermal sensitivity of this miRNAs in the gonads. In all, the identification of these miRNAs may serve as potential epimarkers for predicting past environmental events based on the sexual fish phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing analysis showed that 175 miRNAs were altered after heat stress (mice were placed in a 43°C water bath for 25 min). Among the altered miRNAs, miR-143-3p has been identified as a key regulatory factor that affects spermatogenesis under heat stress ( 32 ).…”
Section: Mirnas and Abnormal Sperm Qualitymentioning
confidence: 99%
“…Recent scientific inquiries have accentuated the detrimental influence of HS on sperm quality across a spectrum of mammalian species, encompassing dogs [ 17 ], bulls [ 20 ], buffaloes [ 26 ], stallions [ 27 , 28 , 29 ], rabbits [ 30 ], pigs [ 31 ], goats [ 32 ], and human males [ 33 , 34 ]. Remarkably, a recurring theme in these studies underscores the adverse impact of HS-induced oxidative stress and apoptosis on the viability of Sertoli cells, spermatogonial stem cells, Leyding cells, spermatogenesis, and sperm quality [ 15 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Furthermore, recent publications have elucidated a compelling association between sperm quality and environmental temperature in men, underscoring the pervasive implications of environmental factors on male reproductive health [ 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%